2010
DOI: 10.1111/j.1439-0272.2009.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ureaplasma urealyticum infection on the male reproductive system in experimental rats

Abstract: To study the effects of Ureaplasma urealyticum (Uu) infection on the male reproductive system, the mechanism of infertility induced by Uu infection was investigated in experimental rats. Male Sprague-Dowley rats were infected with Uu4 (serotype 4) through repeated natural sexual intercourse for 8 weeks to establish infection. After 8 weeks, the blood samples of the animals were collected and analysed for cytokine production, and the animals were microdissected for the analysis of the reproductive system. Morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
5
0
3
Order By: Relevance
“…Besides, UU is also associated with the male reproductive system and is more prevalent in infertile men than in fertile men [29]. An experimental study on rats has indicated that UU affects the sperm morphology leading to its death [30], though other studies have ruled out any association between UU and adverse fertility outcomes [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, UU is also associated with the male reproductive system and is more prevalent in infertile men than in fertile men [29]. An experimental study on rats has indicated that UU affects the sperm morphology leading to its death [30], though other studies have ruled out any association between UU and adverse fertility outcomes [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Chez le rat, la pré sence d'U. urealyticum induirait des alté rations flagellaires à type d'enroulement ou des flagelles é courté s et une mort spermatique [32].…”
Section: Mycoplasmesunclassified
“…in semen specimens was 39.6% and 19.2% in infertile and control men, respectively [10] . The morphological alterations of spermatozoa induced by UU are the possible factors for male infertility [11] .…”
Section: Introductionmentioning
confidence: 99%